A new landmark for lingual artery identification during transoral surgery: Anatomic‐radiologic study. Issue 5 (25th January 2021) - Gualtieri, Tommaso; Verzeletti, Vincenzo; Ferrari, Marco; Perotti, Pietro; Morello, Riccardo; Taboni, Stefano; Palumbo, Giovanni; Ravanelli, Marco; Rampinelli, Vittorio; Mattavelli, Davide; Paderno, Alberto; Buffoli, Barbara; et al.
Abstract: Background: A landmark for the identification of the lingual artery (LA) through a transoral perspective can provide surgeons with an easy method to prevent and manage intraoperative bleeding during transoral approach to the base of tongue (BOT). Methods: Thirteen tongue and five head and neck specimens were dissected to identify and assess the reliability of the lingual point (LP) as a new landmark for the LA at BOT. The pathway of 42 LAs was radiologically evaluated; axial depth and vertical offset were measured for each LA. Results: Dissection study: a description of LP is provided; the LA was easily identified in all specimens (36/36 sides) using LP as a landmark. Radiologic study: the mean depth of the LA was 4.2 mm, the mean vertical offset was 1.3 mm. Conclusions: LP is a simple and reliable landmark for identification of the LA, potentially helping surgeons to prevent and manage intraoperative bleeding.